Home‐based aerobic exercise and resistance training for severe chronic kidney disease: a randomized controlled trial. Issue 6 (23rd September 2021) - Uchiyama, Kiyotaka; Adachi, Keika; Muraoka, Kaori; Nakayama, Takashin; Oshida, Takuma; Yasuda, Marie; Hishikawa, Akihito; Minakuchi, Hitoshi; Miyashita, Kazutoshi; Tokuyama, Hirobumi; Wakino, Shu; Itoh, Hiroshi
Abstract: Background: The potential effects of aerobic and resistance training in patients with severe chronic kidney disease (CKD) are not fully elucidated. This study investigated the effects of a home‐based exercise programme on physical functioning and health‐related quality of life (HRQOL) in patients with Stage 4 CKD, equivalent to estimated glomerular filtration rate of 15–30 mL/min/1.73 m 2 . Methods: Forty‐six patients with Stage 4 CKD (median age, 73 years; 33 men) were randomly assigned to exercise ( n = 23) and control ( n = 23) groups. Exercise group patients performed aerobic exercise at 40–60% peak heart rate thrice weekly and resistance training at 70% of one‐repetition maximum twice weekly at home for 6 months. Control patients received no specific intervention. Primary outcomes were distance in incremental shuttle walking test and HRQOL assessed using the Kidney Disease Quality of Life—Short Form questionnaire. Secondary outcomes included kidney function assessed with combined urea and creatinine clearance, urinary biomarkers, and anthropometric and biochemical parameters associated with CKD. Results: Improvement in incremental shuttle walking test was significantly greater in the exercise group compared with controls (39.4 ± 54.6 vs. −21.3 ± 46.1; P < 0.001). Among Kidney Disease Quality of Life domains, significant mean differences were observed between the exercise group and the control group in work status, quality of social interaction, and kidney disease component summary outcomes (12.76 ± 5.76, P = 0.03; 5.97 ± 2.59, P = 0.03; and 4.81 ± 1.71, P = 0.007, respectively). There were greater reductions in natural log (ln)‐transformed urinary excretion of liver‐type fatty acid‐binding protein, ln serum C‐reactive protein, and acylcarnitine to free carnitine ratio in the exercise group compared with controls, with significant between‐group differences of −0.579 ± 0.217 ( P = 0.008), −1.13 ± 0.35 ( P = 0.003), and −0. 058 ± 0.024 ( P = 0.01), respectively. Conclusions: Our 6 month home‐based exercise programme improved aerobic capacity and HRQOL in patients with Stage 4 CKD, with possible beneficial effects on kidney function and CKD‐related parameters.